NIAT ADOPSI TEKNOLOGI ONLINE GROCERY SHOPPING: EKSTENSI TECHNOLOGY ACCEPTANCE MODEL - Hotna Marina Sitorus; Christa Vania (Universitas Katolik Parahyangan, 2022)
The purpose of this paper is to study factors affecting customer intention to adopt Online Grocery Shopping (OGS) technology. OGS is a service provided by supermarket which enables customers to purchase groceries online. While OGS services offer various benefits, the adoption in Indonesia is still low. The proposed model is developed by extending Technology Acceptance Model with compatibility, visibility, social influence and perceived risk. The model is evaluated using partial least square structural equation modeling (PLS-SEM) based on 108 valid data collected from supermarket customers. The findings show that the customers’ intention to adopt OGS is significantly affected by perceived usefulness and perceived ease of use. Based on total effect analysis, it was found that the intention to adopt OGS is determined by compatibility, perceived usefulness, perceived ease of use, social influence and perceived risk. Furthermore, the study proposes several recommendations for supermarket managers to improve the adoption of OGS.